O orçamento da política municipal de assistência social como parte constitutiva do orçamento público do município de São Paulo - Akagui, Roseli Yoko (2012)
The present study has as object the analysis of the aspects about the formation of the Municipal Budget Policy of Social Assistance, as a constitutive part of the Public Budget of São Paulo City. For this, it was researched the origin of the Brazilian Public Budget, and the manner how your path was and how it is intimately linked to the engendering of the liberal economic system, hegemonic, in Europe and in the United States, and of the direct influence in the formation of the economic history from the Brazilian capitalist state